Qualitative Economics and the Stability of Equilibrium - Quirk, James; Ruppert, Richard (Review of Economic Studies, 1965)
James Quirk, Richard Ruppert; Qualitative Economics and the Stability of Equilibrium*, The Review of Economic Studies, Volume 32, Issue 4, 1 October 1965,